2021
DOI: 10.3390/foods10020397
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation Pattern of Amygdalin and Prunasin and Its Correlation with Fruit and Kernel Agronomic Characteristics during Apricot (Prunus armeniaca L.) Kernel Development

Abstract: To reveal the accumulation pattern of cyanogenic glycosides (amygdalin and prunasin) in bitter apricot kernels to further understand the metabolic mechanisms underlying differential accumulation during kernel development and ripening and explore the association between cyanogenic glycoside accumulation and the physical, chemical and biochemical indexes of fruits and kernels during fruit and kernel development, dynamic changes in physical characteristics (weight, moisture content, linear dimensions, derived par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 70 publications
5
15
0
Order By: Relevance
“…On the other hand, both the apple seeds and the samples of the genus Prunus presented lower amounts of prunasin than amygdalin, in many cases less by an order of magnitude, with values between 0.3 mg/g in several apple seeds and 2.2 mg/g in a cherry sample (Table 5). These results are in agreement with those reported in the bibliography, although the number of references is small [15,22]. However, Senica et al [34] showed that the main cyanogenic glycoside in Golden Delicious seeds from Azerbaijan and Russia was prunasin (1.32 mg/g and 0.91 mg/g).…”
Section: Cyanogenic Glycosides Contents In the Analyzed Samples 241 Rosaceasupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, both the apple seeds and the samples of the genus Prunus presented lower amounts of prunasin than amygdalin, in many cases less by an order of magnitude, with values between 0.3 mg/g in several apple seeds and 2.2 mg/g in a cherry sample (Table 5). These results are in agreement with those reported in the bibliography, although the number of references is small [15,22]. However, Senica et al [34] showed that the main cyanogenic glycoside in Golden Delicious seeds from Azerbaijan and Russia was prunasin (1.32 mg/g and 0.91 mg/g).…”
Section: Cyanogenic Glycosides Contents In the Analyzed Samples 241 Rosaceasupporting
confidence: 88%
“…In the present study, the values were found to be even higher. Several authors have described important differences between bitter and sweet varieties of apricot [22,27,28] with values between undetectable and 70 mg/g, the content of amygdalin being higher in bitter varieties than in sweet ones. High ranges of variability have also been found for amygdalin in cherry, with values between 0.732 [15] and 65 mg/g [29], which places the content of the samples analyzed in this work (8.2-12.6 mg/g) in the middle range.…”
Section: Cyanogenic Glycosides Contents In the Analyzed Samples 241 Rosaceamentioning
confidence: 99%
See 1 more Smart Citation
“…At FZHY doses of 400 and 1,200 mg/kg, the equivalent amygdalin doses administered were 269.1 and 807.4 ng/kg, while the prunasin content was much lower, at 10.8 and 32.5 ng/kg, respectively. Prunasin is a metabolite of amygdalin (Deng et al, 2021 ). The C max values of amygdalin after FZHY administration at doses of 400 mg/kg (6.65 ± 1.15, 8.73 ± 3.43, and 6.85 ± 2.72 ng/ml) and 1,200 mg/kg (21.95 ± 7.41, 43.50 ± 11.82, and 25.43 ± 14.72 ng/ml) were much lower than those of prunasin at doses of 400 mg/kg (94.08 ± 45.20, 93.78 ± 52.37 and 102.25 ± 38.94 ng/ml) and 1,200 mg/kg (217.55 ± 77.98, 223.43 ± 50.17 and 204.08 ± 36.31 ng/ml), on days 1, 15 and 28, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Prunasin is a metabolite of amygdalin (Deng et al, 2021). The C max values of amygdalin after FZHY administration at doses of 400 mg/kg (6.65 ± 1.15, 8.73 ± 3.43, and 6.85 ± 2.72 ng/ml) and 1,200 mg/kg (21.95 ± 7.41, 43.50 ± 11.82, and 25.43 ± 14.72…”
Section: Toxicokinetic Parameters Of Amygdalin and Prunasinmentioning
confidence: 99%